The feedback loop between calcineurin, calmodulin-dependent protein kinase II, and nuclear factor of activated T-cells regulates the number of GABAergic neurons during planarian head regeneration - Zhen, Hui; Zheng, Mingyue; Geng, Huazhi; Song, Qian; Gao, Lili; Yuan, Zuoqing; Deng, Hongkuan; Pang, Qiuxiang; Zhao, Bosheng (Frontiers in Molecular Neuroscience, 2022)
Disturbances in the excitatory/inhibitory balance of brain neural circuits are the main source of encephalopathy during neurodevelopment. Changes in the function of neural circuits can lead to depolarization or repeat rhythmic firing of neurons in a manner similar to epilepsy. GABAergic neurons are inhibitory neurons found in all the main domains of the CNS. Previous studies suggested that DjCamkII and DjCaln play a crucial role in the regulation of GABAergic neurons during planarian regeneration. However, the mechanisms behind the regeneration of GABAergic neurons have not been fully explained. Herein, we demonstrated that DjCamkII and DjCaln were mutual negative regulation during planarian head regeneration. DjNFAT exerted feedback positive regulation on both DjCaln and DjCamkII. Whole-mount in situ hybridization (WISH) and fluorescence in situ hybridization (FISH) revealed that DjNFAT was predominantly expressed in the pharynx and parenchymal cells in intact planarian. Interestingly, during planarian head regeneration, DjNFAT was predominantly located in the newborn brain. Down-regulation of DjNFAT led to regeneration defects in the brain including regenerative brain became small and the lateral nerves cannot be regenerated completely, and a decrease in the number of GABAergic neurons during planarian head regeneration. These findings suggest that the feedback loop between DjCaln, DjCamkII, and DjNFAT is crucial for the formation of GABAergic neurons during planarian head regeneration.